2005
DOI: 10.1007/s10695-006-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone modulation of ovarian recrudescence of air-breathing catfish Clarias gariepinus

Abstract: In the present study, thiourea-induced thyroid hormone depletion and thyroxine (T(4)) 'overdose' were used as a strategy to understand the influence of thyroid hormones on ovarian recrudescence of juvenile (3-months-old), immature (8-months-old) and adult (1-year-old) air-breathing catfish, Clarias gariepinus. Thiourea-induced thyroid hormone depletion in juvenile catfish impaired ovarian development, but no significant effect was observed in immature catfish and during late stage of ovarian recrudescence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Moreover, the THs may also play critical roles in normal reproduction, sex steroids levels, and expression of steroidogenic enzyme genes [54]. The previous studies have demonstrated that T4 administration in female catfish enhanced the growth rate of ovarian follicles and entry of oocytes into the maturational phase compared with controls in the preparatory phase [55]. In the present study, the increase of maturing oocytes accompanied by an increased in plasma T4 were also observed in the 10 lg/L treatment group.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the THs may also play critical roles in normal reproduction, sex steroids levels, and expression of steroidogenic enzyme genes [54]. The previous studies have demonstrated that T4 administration in female catfish enhanced the growth rate of ovarian follicles and entry of oocytes into the maturational phase compared with controls in the preparatory phase [55]. In the present study, the increase of maturing oocytes accompanied by an increased in plasma T4 were also observed in the 10 lg/L treatment group.…”
Section: Discussionsupporting
confidence: 74%
“…(3) Exposure to cortisol results in an increase of the androgen-related machinery and subsequent masculinization in fish (2527, 84), and mammals (32). (4) Exposition of thyroid hormones could inhibit the aromatase (P450arom/ cyp19a1 ) activity or expression in fish (36, 85), amphibians (46, 47), and mammals (58, 59, 75). TRH, thyrotropin-releasing hormone; Dio1, deiodinase type 1; Dio2, deiodinase type 2; T4, thyroxine; ACTH, pituitary adrenocorticotropic hormone; T (testosterone) 11β-HSD2, type 2 isozyme of 11β-hydroxysteroid dehydrogenase; 11-KT, 11-ketotestosterone; 5α-DHT, 5α-dihydrotestosterone.…”
Section: Hypothalamic Regulation Of Thsmentioning
confidence: 99%
“…Thyroid hormone receptors are present on teleost ovarian and testicular cells (Nelson and Habibi 2009) and goitrogens affect gonadal development in fishes including increased numbers of Sertoli and germ cells in tilapia ( Oreochromis niloticus ) exposed to thiouracil (PTU) (Matta et al, 2002) and impaired testicular and ovarian recrudescence in catfish ( Clarias gariepinus ) exposed to thiourea (Supriya et al, 2005; Swapna et al, 2006). Perchlorate causes a female bias in the sex ratio of zebrafish (Mukhi et al, 2007a; Sharma and Patiño, 2013), while evidence of masculinization was found in stickleback (Bernhardt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%